Voided Urinary Microbiota Is Stable Over Time but Impacted by Post Void Storage - Caspar Bundgaard-Nielsen; Caspar Bundgaard-Nielsen; Nadia Ammitzbøll; Nadia Ammitzbøll; Yusuf Abdi Isse; Yusuf Abdi Isse; Abdisalam Muqtar; Abdisalam Muqtar; Ann-Maria Jensen; Peter D. C. Leutscher; Peter D. C. Leutscher; Peter D. C. Leutscher; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: New sensitive techniques have revealed a thriving bacterial community in the human urinary tract, challenging the perception that urine in healthy humans is sterile. While the functional role of this urinary microbiota is unknown, dysbiosis has been linked to urgency urinary incontinence and risk of urinary tract infections. When comparing studies, it is crucial to account for possible confounders introduced due to methodological differences. Here we investigated whether collection and storage conditions had any impact on the urinary microbial composition.Results: For comparison of different storage conditions, midstream urine was collected from five healthy adult female donors and analyzed by 16S rRNA gene sequencing. Samples stored at −80 and −20°C, but not 4°C, were found to be comparable to freshly handled voided urine. Using the same methods, the daily or day-to-day variation in urinary microbiota was investigated in 19 healthy donors, including four women, five men, five girls, and five boys. Apart from two male adult donors, none of the tested conditions gave rise to significant differences in alpha and beta diversities between individuals.Conclusion: The composition of voided urinary microbiota was found to be effectively maintained by freezing, but not storage at 4°C. In addition, we did not observe any intrapersonal daily or day-to-day variations in microbiota composition in women, girls or boys. Together our study supports present methodologies that can be used in future studies investigating the urinary microbiota.